PENGARUH KUALITAS LAPORAN KEUANGAN DAN DEBT MATURITY TERHADAP EFISIENSI INVESTASI DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI: STUDI PADA PERBANKAN GO PUBLIC DI INDONESIA - Muhammad Dedat Dingkorici Akasumbawa; Slamet Haryono (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2021)
The purpose of this study is to test whether variable quality of financial statements, debt maturity and good corporate governance as moderating the quality of financial statements affect investment efficiency. This study used a panel data model with 40 banking samples going public in Indonesia in 2015-2019. The results showed that the quality of financial statements has a significant positive effect on investment efficiency. Debt maturity shows a positive influence on investment efficiency. However, good corporate governance has no effect in moderating the quality of financial statements with investment efficiency.